Design and codify of the test of the nearby shooting accuracy of goal area lineof the handball players - Khaleel Fathi, Moushriq (International Journal of Psychosocial Rehabilitation, 2020)
Design and codify the test of the nearby shooting accuracy of the goal area line of the handball players. The use of modern methods in measuring the accuracy of correction for the players of the circle with handball contributes and helps coaches and researchers to stand on the level of the players by codifying and designing new tests, especially to measure the accuracy of correction on the goal, hence the importance of the research, and the research problem is summarized in that the most available tests used in research The previous ones to measure near accuracy, the recent developments in the game do not serve as a result of the recent amendments to the rules of the game, and most of them are tests far from using modern methods and devices in measuring the accuracy of aiming Design and codify of the test of the nearby shooting accuracy of goal area line of the handball players to design and codify a special test to measure the accuracy of close aiming On the handball goal, as well as designing a special aid that is attached to the handball goal and divides it to measure the accuracy of proximity, the researcher used the descriptive approach In the survey method for its suitability and search procedures, the research sample consisted of ( 125 ) players from Iraq clubs participating in the Iraqi handball league. The researcher used a new tool to measure the accuracy of close correction and used the percentage, the arithmetic mean, standard deviation, torsion lab, correlation coefficient and testing TAs a statistical means, and he concluded: The tool used in testing the accuracy of close aiming was successful and fulfilled the task, and the test that was designed and codified was also successful and was suitable for the sample and became a standardized test and can be generalized, and the researcher recommended that the tool designed for the test be used in Other tests for its success in measuring the accuracy of correction, and the adoption of the test in scientific research, through which it can determine the level of accuracy of correction for players in the future and can be modified to suit other age groups and for both sexes .